Medievalism and Orientalism - Ganim, J. author. aut Link
XIV, 156 p.
Keywords: This unique study traces fundamental parallels between medieval European and Middle Eastern cultures. By examining sources in cultural history, literature, and architecture, this book reveals mutual influences evident in the development of the current conception of the Middle Ages.